2020
DOI: 10.1007/s40544-020-0428-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic nano-tribological interaction between zinc dialkyldithiophosphate (ZDDP) and methyl oleate for biodiesel-fueled engines

Abstract: In biodiesel-fueled compression-ignition (CI) engines, dilution by unburned biodiesel has been found to have adverse effects on the boundary lubrication properties of additives in fully formulated engine lubricants. Such dilution of engine lubricants could be even more pronounced for CI engines running on higher blend concentrations of biodiesel. Given the nanoscopic nature of the interaction, this study seeks to determine the nano-tribological properties of an engine lubricant additive (e.g., zinc dialkyldith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Nanofluids formed from metal compounds also work well as lubricant additives [84][85][86][87]. Lubrication additives can also be obtained by modifying Zn/ZnO (zinc dialkyl dithiophosphates, ZDDP) [88][89][90][91][92][93][94]. Wu et al [95] synthesized lithium complex grease (LCG) added with carbon black (C), Fe 3 O 4 , and Al 2 O 3 nanoparticles on rolling bearing and found that nanoparticles were beneficial to enhance the friction and wear performance (see Fig.…”
Section: Lubricant Additivesmentioning
confidence: 99%
“…Nanofluids formed from metal compounds also work well as lubricant additives [84][85][86][87]. Lubrication additives can also be obtained by modifying Zn/ZnO (zinc dialkyl dithiophosphates, ZDDP) [88][89][90][91][92][93][94]. Wu et al [95] synthesized lithium complex grease (LCG) added with carbon black (C), Fe 3 O 4 , and Al 2 O 3 nanoparticles on rolling bearing and found that nanoparticles were beneficial to enhance the friction and wear performance (see Fig.…”
Section: Lubricant Additivesmentioning
confidence: 99%
“…Several advanced experimental technologies have been employed to investigate the surface adsorption of OFMs. Atomic Force Microscopy (AFM) has been utilized to measure the morphology and frictional properties of adsorbed films [13][14][15][16][17]. Quartz Crystal Microbalance (QCM) has been adopted to assess not only adsorption mass but also adsorption kinetics [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%